Opportunities and Constraints of Land Management in Local and Regional Development. Integrated Knowledge, Factors and Trade-offs. - (:unkn) unknown (vdf Hochschulverl., 2018)
Land Management is normally embedded in a complex legal context, which frequently consists of contradictory objectives, such as: strengthening of rural areas, satisfying the need for affordable living and commercial space, protecting environment and health, supporting transport infrastructure development, and preserving the landscape. Land management can be understood as a process that comprises coordination of such activities while managing the use and the development of land resources. It can be constrained by the land use specifications resulting from spatial planning process. Along with this, the legal framework often contains generally formulated concepts and open standards, which provide a range of opportunities for realization while balancing the different interests. In this process it is important if and how both constraints and opportunities are recognised by the actors. In this volume this topic is examined from various aspects: first the problems in promoting mutual understanding between researchers and the general public, but also among scientists of different disciplines; second the success requirements of land management instruments as well as unfortunate experience caused by land use changes; third covering land management costs by absorbing value increase and other trade off aspects; and fourth supporting land management by providing geodata with low-cost methods.
Keywords: Raumplanung; Regionalplanung; Flächenmanagement; Landmanagement; Flächennutzung; Flächenrecycling; Siedlungsentwicklung; Stadtentwicklung; Stadterneuerung; Ländlicher Raum; Integrierte Planung; Wissensmanagement; Wissenstransfer; Planungsprozess; Interessenausgleich